Pengaruh Mental Health dan Work Life Balance terhadap Turnover Intention Karyawan Gen Z di Kota Medan - Rasidah Novita Sari; Nabila Khonsaa Adefia; Siti Musfiroh; Fany Cahyaningsi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This paper examines the influence of financial education on personal financial management practices of Generation Z. A quantitative method with a survey approach was used, involving 30 Generation Z respondents (aged 17-25 years) through questionnaires and simple linear regression analysis. The results of the study indicate a significant influence of financial education on wise financial management practices. Generation Z with adequate financial education tends to be more able to budget, save, invest, and avoid impulsive debt. Conversely, the lack of financial education makes them vulnerable to unwise financial decisions. This paper highlights the importance of integrating financial education into the curriculum and self-development programs to improve literacy and healthy financial practices among Generation Z. This study also discusses the challenges faced by Generation Z in managing finances in the digital era, such as a consumptive lifestyle influenced by social media and e-commerce.